The kawayanihan project Miriam R. Ildesa, Raymund Jun T. Oberes, Ann Camille I. Reyes, Dannel P. Subong, Reziah Danielle P. Tablazon, Famela G. Tumaob, Gay Bryll Angelica C. Ulson. - Ildesa, Miriam R.; Oberes, Raymund Jun T.; Reyes, Ann Camille I.; Subong, Dannel P.; Tablazon, Reziah Danielle P.; Famela G. Tumaob; Ulson, Gay Bryll Angelica C. (2016)
The Kawayanihan project strives to become a changemaker in the Philippines by creating innovative solutions using the native spine bamboo (Bombusa blumeana) to address the problems faced by the Filipinos today. By partnering with local bamboo craftsmen, we will be able to constantly develop fresh and new bamboo products that are affordable, efficient and are tailor-made to address the problems of our customers, specifically, those who are members of low-income communities. With today's focus on indigenous technology in solving pressing problems, the Kawayanihan Project will become a benchmark of innovation, nationalism and cooperation. The venture seeks to realize its vision by being first in the market. The native bamboo offers flexibility offers flexibility in transforming into different products all of which are useful ranging from decorative to utility. However, none has maximized the potential of the bamboo. In addition, but building partnerships with government agencies and LGUs, The Kawayanihan project will be able to generate quality products that are indeed feasible and conforming to local and international standards. Our network with industry experts will also enforce our stand in making affordable yet effective products a possibility. Lastly, our stance in making the venture customer-centric will result to products that are specifically designed with our customer's needs and capacity. As a a result, with our target market's nature, our products are expected to be of high quality, affordable, and convenient to use. Carrying the torch for the venture is Kalinaw, a charcoal water filter that seeks to address water insecurity problems of households and communities depending on communal ground water sources, specifically hand water pumps. This product is the driving force in the concretion of the Kawayanihan project. The team discovered a small-scale local bamboo charcoal producer, Mr. Norberto Ceballos. Upon meeting him and sharing visions, the venture decided to pursue the bamboo charcoal water filter as the flag bearer of the newly-formed partnership. Bamboo charcoal is scientifically proven as an effective filter medium, capable of removing impurities and suspended solids from the water, decrease turbidity and in the process, release small increments of minerals to the water which are good for human health. The creation of the product involves lean production processes and environment-friendly design, as the bamboo charcoal is produced from bamboo waste. Our operations highlight a bayanihan system, with our workers simply part-timers, and as a result, supplement their income as bamboo craftsmen. To realize our vision of becoming a change maker in the industry, each member have agreed to contribute to the partnership capital. To supplement this are bank loans and funding support. After the first year of operations, the Kawayanihan project will use a rolling capital system to expand production and fuel research and development for future products. Filter the future. The venture believes that having a secure access to clean water can be instrumental in achieving a better lifestyle and wellness, and as a result, critical in the quest for a better future. This is simply a start for the Kawayanihan project. More than the potential solutions to the needs of our customers, our impact will also be evident in our partner community, where economic, through additional livelihood, social, through skills development and knowledge management, and environmental, through a sustainable business strategy and environment-oriented programs, impact will be achieved with collective efforts with our partner community and external partners.